Faith in Mark: Access to Power and Recognition of Authority - Gottschall, Brendan (Lumen et Vita, 2024)
Many scholars agree that discipleship is a central message in the Gospel of Mark. Despite this recognition, the theme of faith remains an under-appreciated aspect of discipleship. In Mark’s Gospel, the disciples and those closest to Jesus are chastised for their lack of faith while the faith of others is often praised and rewarded with healings. A close reading of all the instances of the πιστ-stem words reveals that Mark uses faith in two senses, both of which shed light on the meaning of discipleship: first, faith as trust in Jesus’ power is a prerequisite for access to healing and miracle-working; second, believing means recognizing Jesus’ authority as the Messiah. Moreover, the author of the Longer Ending picked up on Mark’s two-fold use of faith and cast believing as recognizing Jesus’ resurrection which manifests both his miraculous power and authority as Messiah.